E-108 Ruptured intracranial aneurysm presenting as isolated acute subdural hemorrhage. (23rd July 2022) - Babici, D; Johansen, P; Newman, SL; Packer, E; Snelling, B
Abstract : Introduction: Ruptured intracranial aneurysms are often associated with serious neurologic sequelae, often as a result of subarachnoid or intraparenchymal hemorrhage. Less commonly, ruptured intracranial aneurysms can lead to subdural hemorrhage. However, the characteristic clinical presentation and optimal treatment of associated subdural hemorrhage are unclear due to the paucity of such cases that exist in the current literature. Affected patients may complain of nonspecific symptoms such as headaches, nausea, and confusion. Because of the severity of the disease, rapid diagnosis and intervention is required to lower the high morbidity and mortality rates. Commonly used treatment options include endovascular coiling and microsurgical clipping. Neuroendovascular surgery is often preferred, especially in aneurysms not amenable to surgical clipping, in poor surgical candidates, and in cases with endovascularly favorable anatomy. Methods: Single case study. Case Description: A 65-year-old female with no known past medical history suddenly developed right-sided weakness and leftward gaze deviation, prompting a stroke alert to be initiated prior to arrival in the ED. Once arrived at the hospital, she became drowsy and unable to follow commands. After several vomiting episodes, she was emergently intubated for airway protection. Her initial blood pressure was 240/120, for which labetalol and nicardipine were administered. CT scan of the head revealed a left-sided subdural hematoma with a left-to-right midline shift and scant subarachnoid hemorrhage in the Sylvan fissure. Given the patient's declining neurological exam and radiographic findings, she was taken to the operating room for emergent evacuation of the subdural hematoma. Following surgery, MRA of the brain was ordered and revealed a left-sided 6mm posterior communicating artery aneurysm. Urgent coil embolization of the aneurysm was successfully performed via right radial artery access with Raymond-Roy class 2 occlusion. In the following days, the patient's right-sided weakness significantly improved, and her sensory examination remained unremarkable with intact deep tendon reflexes. Conclusion: In rare cases, ruptured intracranial aneurysms can be associated with isolated subdural hemorrhage. Common treatment options include endovascular coiling and microsurgical clipping. However, endovascular repair is often preferred especially when the patient may not be able to tolerate a surgical procedure, as was the case with this patient. In this case, the patient presented with stroke-like symptoms and was found to have a subdural hemorrhage. After emergent craniotomy to evacuate the hematoma, successful endovascular coiling was performed, and the patient was stabilized for further management> Disclosures: D. Babici: None. P. Johansen: None. S. L. Newman: None. E. Packer: None. B. Snelling: None.